Hubungan Pendidikan Dengan Pengetahuan Tentang Aromaterapi Pada Ibu Hamil Di Wilayah Kerja Puskesmas Bergas - Khairani, Alya Fernanda; widayati, Widayati; Windayanti, Hapsari (Midwifery Care Journal, 2025)
translator AfrikaansAlbanian - shqipeArabic - ‎‫العربية‬‎Armenian - ՀայերէնAzerbaijani - azərbaycancaBasque - euskaraBelarusian - беларускаяBengali - বাংলাBulgarian - българскиCatalan - catalàChinese - 中文（简体中文）Chinese - 中文 (繁體中文)Croatian - hrvatskiCzech - češtinaDanish - danskDutch - NederlandsEnglishEsperanto - esperantoEstonian - eestiFilipinoFinnish - suomiFrench - françaisGalician - galegoGeorgian - ქართულიGerman - DeutschGreek - ΕλληνικάGujarati - ગુજરાતીHaitian Creole - kreyòl ayisyenHebrew - ‎‫עברית‬‎Hindi - हिन्दीHungarian - magyarIcelandic - íslenskaIndonesian - Bahasa IndonesiaIrish - GaeilgeItalian - italianoJapanese - 日本語Kannada - ಕನ್ನಡKorean - 한국어Latin - Lingua LatinaLatvian - latviešuLithuanian - lietuviųMacedonian - македонскиMalay - Bahasa MelayuMaltese - MaltiNorwegian - norskPersian - ‎‫فارسی‬‎Polish - polskiPortuguese - portuguêsRomanian - românăRussian - русскийSerbian - СрпскиSlovak - slovenčinaSlovenian - slovenščinaSpanish - españolSwahili - KiswahiliSwedish - svenskaTamil - தமிழ்Telugu - తెలుగుThai - ไทยTurkish - TürkçeUkrainian - українськаUrdu - ‎‫اردو‬‎Vietnamese - Tiếng ViệtWelsh - CymraegYiddish - יידיש  Double-click Select to translate  Knowledge is very closely related to education, people with higher education are expected to have wider knowledge. The level of education affects the understanding and use of aromatherapy among pregnant mothers through a variety of ways, ranging from the ability to access and understand information to the practices of use and safety evaluation. Aromatherapy itself has benefits for pregnant mothers in managing symptoms such as stress, nausea, and pain. To find out the relationship between education and knowledge about aromatherapy in pregnant mothers in the work area of Bergas health center. This research uses a correlation analytical design with a quantitative approach. The population in this study was pregnant women with a total of 120 pregnant women. The sample in this study was pregnant women with a total of 92 respondents using the formula slovin, sampling techniques with techniques purposive sampling by design cross-sectional, data collection tools use questionnaires, analysis tests use tests chi square. The results of the study showed a large height of middle-educated mothers of 36 pregnant women (39.1) and a large number of mothers with sufficient knowledge of 47 pregnant mothers (51.1%). The result of the analysis of the chi-square test there was a significant relationship between education and knowledge of aromatherapy in pregnant mother in the working area Bergas health center with p-value (0,001) α (0,05). The higher the level of education of pregnant women, the better the level of knowledge about aromatherapy in pregnant women.